Peningkatan Efisiensi Produksi Menggunakan Value Stream Mapping Dan 5S Pada PT. ABC - Bambang; Arif Rahman; Joni Apriyanto (BULLET : Jurnal Multidisiplin Ilmu, 2026)
Industrial competition requires companies to continuously improve production efficiency and reduce waste in their operational processes. This study aims to identify waste in the production process and propose improvement strategies using the Lean Manufacturing approach. The research was conducted at PT XYZ, a batik manufacturing company that implements a make‑to‑order production system. The methods used in this study are Value Stream Mapping (VSM) to analyze material and information flow and the 5S method (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) to improve workplace organization. Data were collected through observation, interviews, and documentation of the production process. The results show several non‑value‑added activities such as waiting time, excessive inventory, and inefficient workplace layout. After implementing improvements using VSM and 5S, the total production time decreased from 485 minutes to 350 minutes. These results indicate that the integration of VSM and 5S can significantly improve production efficiency.